Gestantes com atendimento odontológico na capital paraense em tempos de Previne Brasil - REIS, Adryane de Paula Barbosa (2023)
This article describes and analyzes the results corresponding to the third component indicator of the performance-based payment guideline of the Primary Health Care Financing Program "Previne Brasil" during the three quadrimesters of the year 2022. The objective is to evaluate the performance of the dental indicator of Previne Brasil: the proportion of pregnant women who received dental care in the health units of the city of Belém, the capital of the state of Pará. The study conducts a three-way analysis of variance (ANOVA) using the R software among the quadrimester results of each team indicator during the year 2022, from a quadrimester and district perspective. These results demonstrate the efficiency of the Ribeirinha Family Health team in the face of the difficulties encountered in the region and highlight the positive impact of the university as a promoter of progress in the administrative district where it is located.